2018
DOI: 10.1097/mpa.0000000000001182
|View full text |Cite
|
Sign up to set email alerts
|

Imaging and Cytopathological Criteria Indicating Malignancy in Mucin-Producing Pancreatic Neoplasms

Abstract: Objectives This study aims to evaluate the performance of clinical, imaging, and cytopathological criteria in the identification of high-grade dysplasia/carcinoma (HGD/Ca) in pancreatic mucin-producing cystic neoplasms. Methods Sixty-eight consecutive, histopathologically confirmed mucin-producing cystic neoplasms, evaluated by endoscopic ultrasound-guided fine-needle aspiration, were enrolled; specifically, 39 branch duct intraductal papillary mucinous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Hence, evidence suggests the proposed WHO reporting system, with its two new "pancreatic neoplasm, low-risk/grade" and "pancreatic neoplasm, high-risk/grade" categories, could potentially stratify pancreatic neoplasms (conservative management vs potential surgery) more effectively than the existing PSC system, as highrisk/grade cystic lesions have been associated with a much higher ROM. The criteria to detect HGA in pancreatic cystic fluid cytology-high nuclear/cytoplasmic ratio, nuclear membrane irregularities, hyper-or hypochromasia, and necrosis [26,27]-have been reported to be sensitive and specific to predict HGD or malignancy in histology [28], while demonstrating good interobserver reproducibility [29,30]. Notably, a recent immunohistochemical marker, the Das-1, has shown to be highly accurate detecting high-risk mucinous pancreatic cysts, especially when combined with cytology [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Hence, evidence suggests the proposed WHO reporting system, with its two new "pancreatic neoplasm, low-risk/grade" and "pancreatic neoplasm, high-risk/grade" categories, could potentially stratify pancreatic neoplasms (conservative management vs potential surgery) more effectively than the existing PSC system, as highrisk/grade cystic lesions have been associated with a much higher ROM. The criteria to detect HGA in pancreatic cystic fluid cytology-high nuclear/cytoplasmic ratio, nuclear membrane irregularities, hyper-or hypochromasia, and necrosis [26,27]-have been reported to be sensitive and specific to predict HGD or malignancy in histology [28], while demonstrating good interobserver reproducibility [29,30]. Notably, a recent immunohistochemical marker, the Das-1, has shown to be highly accurate detecting high-risk mucinous pancreatic cysts, especially when combined with cytology [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Salla et al found that the presence of mural nodule was associated with increased risk of high grade dysplasia/carcinoma in patients with branch duct IPMN. [26] In a recent multicenter study by Postelwait et al; male sex, pancreatic head, and neck location, increased size of the lesion, presence of solid component, or mural nodule, and duct dilatation were independently associated with malignancy in patients with pancreatic mucinous cystic neoplasms. [27] Several societies and associations have formulated guidelines for evaluation, management and follow-up of cystic pancreatic lesions with some differences and similarities between them.…”
Section: Discussionmentioning
confidence: 91%
“…For instance, the Fukuoka guidelines enlist distinct “high-risk stigmata” and “worrisome features”, which should be considered before deciding to surgically excise a pancreatic cystic lesion or recommend close follow-up. The presence of suspicious or positive cytology (microscopic features consistent with HGD or invasion) also triages eligible patients for surgery [ 131 , 132 ]; however, although pancreatic cyst cytology has a high specificity, its sensitivity is considered suboptimal [ 129 ]. Of interest, a recent meta-analysis on the Fukuoka and AGA guidelines found they both exhibited an inadequate diagnostic accuracy to distinguish between low- and high-risk pancreatic cysts [ 133 ].…”
Section: Discussionmentioning
confidence: 99%